Right-wing populism and safe identities. Issue 1 (2nd January 2020) - Lobban, Rosemary; Luyt, Russell; Martin, Sam; Brooks, Ashley; McDermott, Daragh; Zawisza-Riley, Magdalena
ABSTRACT: Recent events such as the US presidential campaign have polarised public opinion, particularly in terms of support for 'populist' political figures, e.g. Donald Trump, and the seemingly non-egalitarian ideologies that they promote. One might anticipate that disempowered social groups, such as women or sexual minorities, would reject 'rightwing populism', as it rarely appears to advocate their interests or facilitate their empowerment. Yet the existence of movements like 'Gays for Trump' and '#WomenWhoVoteTrump' indicate more complex patterns of support. How might we understand this from gender and sexualities perspectives? This paper presents the proceedings of a round table discussion. Our contributors, members of a crossinstitutional social psychological Gender and Sexualities Research Group, each presented a brief five-minute interpretation of the phenomenon. They did so from gender and/or sexualities perspectives, drawing upon different social psychological theory. A chaired debate followed. Key themes from the round table are identified which are potentially helpful in understanding the phenomenon. The broader implications of these themes for practice and theory are considered in terms of the concept of 'safe identities'.